2017
DOI: 10.3233/jad-161163
|View full text |Cite
|
Sign up to set email alerts
|

A 3-Month Aerobic Training Program Improves Brain Energy Metabolism in Mild Alzheimer’s Disease: Preliminary Results from a Neuroimaging Study

Abstract: In mild AD, aerobic training improved brain energy metabolism by increasing ketone uptake and utilization while maintaining brain glucose uptake, and could potentially be associated with some cognitive improvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 54 publications
0
30
0
Order By: Relevance
“…Ketones may counteract AD pathogenesis because a ketone ester diet that elevates BHB more than tenfold lessens Aβ and tau pathologies and ameliorates behavioural abnormalities in 3xTg-AD mice 143 . Moreover, Castellano et al recently reported that a 3-month aerobic training (brisk walking) programme increased brain cell ketone utilization in patients with AD threefold without affecting cerebral glucose utilization 144 , which may be one reason that aerobic exercise can protect the brain against AD. That IF may be another approach for subjects at risk of or with AD is suggested by a study using 11 C-acetoacetate positron emission tomography (PET) imaging that showed that within 48 hours of the onset of fasting, there is a sevenfold to eightfold increase in brain uptake of ketones 4,145 .…”
Section: Ims and Neurological Disordersmentioning
confidence: 99%
“…Ketones may counteract AD pathogenesis because a ketone ester diet that elevates BHB more than tenfold lessens Aβ and tau pathologies and ameliorates behavioural abnormalities in 3xTg-AD mice 143 . Moreover, Castellano et al recently reported that a 3-month aerobic training (brisk walking) programme increased brain cell ketone utilization in patients with AD threefold without affecting cerebral glucose utilization 144 , which may be one reason that aerobic exercise can protect the brain against AD. That IF may be another approach for subjects at risk of or with AD is suggested by a study using 11 C-acetoacetate positron emission tomography (PET) imaging that showed that within 48 hours of the onset of fasting, there is a sevenfold to eightfold increase in brain uptake of ketones 4,145 .…”
Section: Ims and Neurological Disordersmentioning
confidence: 99%
“…Intermittent energy restriction improves cognitive and motor performance, and can protect neurons against dysfunction and degeneration in animal models of epilepsy, stroke, PD, and AD (Bruce-Keller et al, 1999; Duan and Mattson, 1999; Yu and Mattson, 1999; Halagappa et al, 2007; Alirezaei et al, 2010; Fann et al, 2014; Parikh et al, 2016; Prehn et al, 2017). Regular aerobic exercise, which is necessary for the survival of many animals, can also enhance brain health throughout the life course; exercise reduces anxiety and improves cognition in laboratory animals and human subjects (Intlekofer and Cotman, 2013; Boraxbekk et al, 2016; Castellano et al, 2017; Chirles et al, 2017; Raichlen and Alexander, 2017). While fasting and vigorous exercise are different challenges to the body and brain, emerging findings are revealing that they each elicit similar adaptive cellular responses that can enhance neuroplasticity and stress resistance.…”
Section: Metabolic Factors Can Accelerate or Decelerate Brain Agingmentioning
confidence: 99%
“…Therefore, regular physical exercise can be recommended as a prevention strategy for AD as well as one type of treatment for pre-clinical and late stage AD. Aerobic exercise in early AD is particularly associated with benefits in cognitive functioning [136,137,138]. …”
Section: The Effect Of Lifestyle and Diet On The Genesis/progressimentioning
confidence: 99%